Immune Thrombocytopenia (Itp) In Emergency Medicine: Life Sciences-Thrombocytopenia - Salah Hussain, Mohammed; Ghadah Mohammedanas M, Makhdum; Abdullah Mohammed M, Alsharif; Abdullah Musnad Alshammari , Abdulmajeed; Raghad Abdullah M , Mohammed; Abdullah H Althobaiti , Alanoud; Zainab Atallah S , Albalawi; Amal Mohammed H, Labani; Abdullah Saud A, Alshebli; Abdullah Mohammed, Alawad; Hamad Alsidrani, Rayan; Thawab Muthyib T , Alsubaie; et al. (International Journal of Life Science and Pharma Research, 2022)
Immune Thrombocytopenia (ITP) is an autoimmune disorder characterised by a low platelet countless than 100? ×? 10^9/L, purpura, and hemorrhagic episodes induced by antiplatelet autoantibodies without anemia or leukopenia. Immune thrombocytopenia (ITP) occurs in 2 to 4/100? 000 adults. A wide range of signs and symptoms, from modest mucocutaneous petechiae to severe, life-threatening organ haemorrhage, are seen in ITP patients. they may present to the emergency department (ED) with life-threatening bleeding as a result of their thrombocytopenia. ITP has two distinct clinical syndromes, manifesting as an acute condition in children and a chronic condition in adults. IgG autoantibodies make circulating platelets more sensitive. It causes these cells to be removed more quickly by antigen-presenting cells (macrophages) of the spleen, and occasionally the liver or other components of the monocyte-macrophage system. Current evidence supports alternatives to splenectomy for second-line management of patients with persistently low platelet counts and bleeding. By increasing platelet production, bone marrow compensates for platelet breakdown. Immune Thrombocytopenia most commonly arises within a few weeks after a viral infection in healthy children and young adults. Immunosuppressive treatment is usually effective in treating ITP. Many patients with ITP require no emergent treatment. However, the emergency physician should start treatment with a platelet transfusion, corticosteroids, and intravenous immune globulin (IVIG) as soon as the patient with suspected ITP arrives at the ED with serious haemorrhage.The diagnosis is usually made by ruling out all known causes of thrombocytopenia. This review aims to summarize current evidences regarding prevalence, causes, diagnosis and management of immune thrombocytopenia. Keywords:,